Hrvatska standardnojezična norma u promidžbenim tiskanim katalozima trgovačkih lanaca - Smajić, Dubravka; Vodopija, Irena (SlavVaria, 2026)
The Croatian standard language norm in promotional printed catalogues of retail chains. This paper explores the language used in promotional printed materials of retail chains, focusing on how it differs from the rules of standard Croatian. It especially analyses the frequency and types of language errors and explains what the language norm is, how language errors are classified, and what the main features of advertising texts are, including their purpose and writing style. Paper analysis the advertising catalogs of ten retail chains in Croatia. The most common errors found were in spelling and word choice, while grammar errors were less frequent, such as those in pronunciation, word forms, sentence structure, and word creation. The results show that the language rules are not applied consistently and that foreign languages, especially English, have a strong influence on the way advertising messages are written in these catalogs.